Indic Elements in Indonesian Arts and Literature: Shared Heritage Between India and Indonesia - Jha, Gautam Kumar (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2022)
Indic-Belt or the Greater India is the geographical region where Bharat’s knowledge tradition spread and influenced the local community in terms of language, culture, religions, practices and social values. Southeast Asia, especially Indonesia has been the region that received more Indic knowledge than any other parts of the world due to the easy accessibility to the land and sea routes. This Indic influence is visible in many art forms and folklore due to a long period of rules of Hindu-Buddhist kingdoms. This study aims at exploring the presence of Indic elements in Indonesian artworks, old buildings and folklore. This paper is based on a qualitative descriptive study in which the data was collected through literature study. The study found that Indian epics such as Ramayana and Mahabharata have greatly influenced the literary tradition in Indonesia, as it was present in the forms of puppets, woodcrafts, painting and batik. In addition, Indonesian-present vocabulary ”˜Esa’ (singular) to describe the concept of oneness of God came from the Sanskrit word ”˜ish’ which was carried out by the Indic permeate to Indonesia. The study suggests that with such influence of Indic culture and tradition to Indonesia, both Indonesia and India shared similar heritage and hence steps to strengthen the cultural bonds between the two nations need to be built and maintained.